KEPEMIMPINAN TRANSFORMASIONAL PROFETIK DALAM MENGEMBANGKAN PESANTREN DI KABUPATEN JEMBER - Umiarso Umiarso (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract Pesantren (Islamic boarding schools) has been continuously aligning its educational system with the needs of society and the times. The development of pesantren is inseparable from the role of kiai in carrying out the institutional transformation. This study focuses on transformational leadership of the kiai in developing the pesantren institution. The results of this study indicate that the concept of developing pesantren is transcultural with the principle of